Des indiens comme nous - Jacquemin, Sylvie (France, 2010)
A group of friends who share a romantic passion for North American natives finally manage to travel to "real" rezervations to meet "real" Indians. Ther romantic visions soon fade when they realize the complexity of life as a Native American in the modern world.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films